Pressure-sensitive adhesive composition and optical member with pressure-sensitive adhesive layer
Patent Information
- Application Number
- JP2021042930
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-03-16
AI Technical Summary
【0008】 本開示の一実施形態によれば、高温耐久性に優れる粘着剤層を形成でき、かつ、塗工性に優れる粘着剤組成物が提供される。 本開示の他の実施形態によれば、高温耐久性に優れる粘着剤層を備える粘着剤層付き光学部材が提供される。
Smart Images

Figure 0007643898000001 
Figure 0007643898000002 
Figure 0007643898000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a pressure-sensitive adhesive composition and an optical member with a pressure-sensitive adhesive layer. [Background technology]
[0002] Many portable electronic devices such as mobile phones and mobile terminals incorporate liquid crystal display devices. In general, liquid crystal display devices include a liquid crystal cell in which a liquid crystal layer is sandwiched between two glass substrates, and polarizing plates disposed on both sides of the liquid crystal cell. In order to ensure the visibility of the liquid crystal display device, the liquid crystal cell and the polarizing plates are generally bonded together via an adhesive layer formed of an acrylic adhesive.
[0003] For example, Patent Document 1 discloses a pressure-sensitive adhesive suitable for optical members such as polarizing plates, which is obtained by curing an adhesive composition containing a (meth)acrylic acid ester polymer (A) having a weight-average molecular weight of 900,000 to 3,000,000 and containing a monomer having an alicyclic structure as a monomer unit constituting the polymer, a crosslinking agent (B), and an active energy ray-curable component (C) which is a polyfunctional acrylate monomer having a molecular weight of less than 1,000, by irradiation with active energy rays, wherein the content of the active energy ray-curable component (C) in the adhesive composition is 1 part by mass to 20 parts by mass per 100 parts by mass of the (meth)acrylic acid ester polymer (A), and the gel fraction of the pressure-sensitive adhesive is 30% to 90%. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6502999 Summary of the Invention [Problem to be solved by the invention]
[0005] Pressure-sensitive adhesive compositions used for optical members such as polarizing plates are required to be capable of forming pressure-sensitive adhesive layers that are excellent in the property of suppressing foaming, lifting, and peeling (hereinafter also referred to as "high-temperature durability") even when exposed to a high-temperature (e.g., 105°C; the same applies below) environment. Moreover, a pressure-sensitive adhesive composition is generally required to have excellent coatability.
[0006] An object of one embodiment of the present disclosure is to provide a pressure-sensitive adhesive composition that can form a pressure-sensitive adhesive layer having excellent high-temperature durability and also has excellent coatability. Another problem to be solved by another embodiment of the present disclosure is to provide a pressure-sensitive adhesive layer-attached optical member that includes a pressure-sensitive adhesive layer that is excellent in high-temperature durability. [Means for solving the problem]
[0007] Specific means for solving the problems include the following aspects. <1> a (meth)acrylic copolymer comprising a structural unit derived from a (meth)acrylic acid alkyl ester monomer, a structural unit derived from a monomer having a carboxy group, and a structural unit derived from a polyfunctional (meth)acrylic acid ester monomer, the content of the structural unit derived from the polyfunctional (meth)acrylic acid ester monomer being 0.001% by mass to 0.05% by mass relative to the total structural units; A cross-linking agent; Including, The pressure-sensitive adhesive composition, wherein the content of the crosslinking agent is 0.05 parts by mass or more based on 100 parts by mass of the (meth)acrylic copolymer. <2> The polyfunctional (meth)acrylic acid ester monomer is a bifunctional (meth)acrylic acid ester monomer. <1> The pressure-sensitive adhesive composition according to claim 1. <3> The molecular weight of the polyfunctional (meth)acrylic acid ester monomer is in the range of 200 or more and less than 1000. <1> or <2> The pressure-sensitive adhesive composition according to claim 1. <4> The (meth)acrylic copolymer has a weight average molecular weight [Mw] of 1.4 million to 2.2 million, and a ratio [Mz / Mw] of the z-average molecular weight [Mz] to the weight average molecular weight [Mw] of 2.5 to 4.5. <1> ~ <3> 13. The pressure-sensitive adhesive composition according to claim 12 . <5> The content of the structural units derived from the monomer having a carboxy group in the (meth)acrylic copolymer is 0.1% by mass to 5.0% by mass based on the total structural units of the (meth)acrylic copolymer. <1> ~ <4> 13. The pressure-sensitive adhesive composition according to claim 12 . <6> The (meth)acrylic copolymer contains a structural unit derived from a monomer having a hydroxyl group. <1> ~ <5> 13. The pressure-sensitive adhesive composition according to claim 12 . <7> The content of the structural units derived from the monomer having a hydroxyl group in the (meth)acrylic copolymer is 0.1% by mass to 3.0% by mass based on the total structural units of the (meth)acrylic copolymer. <6> The pressure-sensitive adhesive composition according to claim 1. <8> An optical member; provided on the optical member, <1> ~ <7> a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of the above items; An optical member with a pressure-sensitive adhesive layer comprising: Effect of the Invention
[0008] According to one embodiment of the present disclosure, there is provided a pressure-sensitive adhesive composition that can form a pressure-sensitive adhesive layer having excellent high-temperature durability and has excellent coatability. According to another embodiment of the present disclosure, there is provided a pressure-sensitive adhesive layer-attached optical member including a pressure-sensitive adhesive layer having excellent high-temperature durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The pressure-sensitive adhesive composition and the pressure-sensitive adhesive layer-attached optical member of the present disclosure will be described in detail below. The following description of the requirements may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment, and can be modified as appropriate within the scope of the purpose of the present disclosure.
[0010] In the present disclosure, a numerical range indicated using "to" means a range that includes the numerical values before and after "to" as the lower limit and upper limit, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.
[0011] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when the adhesive composition contains multiple substances corresponding to each component, the amount of each component in the adhesive composition means the total amount of the multiple substances present in the adhesive composition, unless otherwise specified.
[0012] In the present disclosure, "(meth)acrylic copolymer" means a copolymer in which the content of structural units derived from monomers having a (meth)acryloyl group is 50 mass% or more of all structural units (i.e., all structural units of the (meth)acrylic copolymer).
[0013] In this disclosure, "(meth)acrylic" is a term that encompasses both "acrylic" and "methacrylic", "(meth)acrylate" is a term that encompasses both "acrylate" and "methacrylate", and "(meth)acryloyl" is a term that encompasses both "acryloyl" and "methacryloyl".
[0014] In this disclosure, "n-" means normal, "i-" means iso, "s-" means secondary, and "t-" means tertiary.
[0015] [Adhesive composition] The pressure-sensitive adhesive composition of the present disclosure comprises a (meth)acrylic copolymer (hereinafter also referred to as a "specific (meth)acrylic copolymer") that contains a constituent unit derived from a (meth)acrylic acid alkyl ester monomer, a constituent unit derived from a monomer having a carboxy group, and a constituent unit derived from a polyfunctional (meth)acrylic acid ester monomer, and the content of the constituent units derived from the polyfunctional (meth)acrylic acid ester monomer is 0.001 mass % to 0.05 mass % based on all constituent units, and a crosslinking agent, the content of the crosslinking agent being 0.05 parts by mass or more based on 100 parts by mass of the (meth)acrylic copolymer. The pressure-sensitive adhesive composition of the present disclosure can form a pressure-sensitive adhesive layer that has excellent high-temperature durability and also has excellent coatability. The reason why the pressure-sensitive adhesive composition of the present disclosure can exhibit such an effect is unclear, but the present inventors speculate as follows, however, the following speculation is not intended to limit the pressure-sensitive adhesive composition of the present disclosure, but is merely an example.
[0016] The (meth)acrylic copolymer contained in the pressure-sensitive adhesive composition of the present disclosure contains a constituent unit derived from a polyfunctional (meth)acrylic acid ester monomer. Since a polyfunctional (meth)acrylic acid ester monomer has many reactive sites and is a highly reactive monomer, when a polyfunctional (meth)acrylic acid ester monomer is used as a raw material monomer, crosslinking between the polyfunctional (meth)acrylic acid ester monomers is likely to occur, and the z-average molecular weight [Mz] of the (meth)acrylic copolymer tends to be high. Note that a high Mz means that the proportion of high molecular weight substances in the entire polymer is high. It is considered that the higher the proportion of high molecular weight substances in the entire polymer, the more complex the entanglement of the polymer chains becomes, and therefore the elastic modulus of the formed pressure-sensitive adhesive layer becomes high. When the elastic modulus of the pressure-sensitive adhesive layer is moderately high, phenomena such as foaming, lifting, and peeling tend not to occur even when the pressure-sensitive adhesive layer is exposed to a high-temperature environment. In the pressure-sensitive adhesive composition of the present disclosure, the (meth)acrylic copolymer contains a specific ratio or more of a structural unit derived from a polyfunctional (meth)acrylic acid ester monomer, so that the proportion of high molecular weight substances in the total polymer is moderately high, and the entanglement of the polymer chains becomes moderately complex. Therefore, it is considered that the elastic modulus of the pressure-sensitive adhesive layer formed is moderately high. In addition, the (meth)acrylic copolymer contained in the pressure-sensitive adhesive composition of the present disclosure contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer and a structural unit derived from a monomer having a carboxy group, which is a crosslinkable functional group, in addition to the structural unit derived from the polyfunctional (meth)acrylic acid ester monomer. Since the pressure-sensitive adhesive composition of the present disclosure contains a specific ratio or more of a crosslinking agent relative to the (meth)acrylic copolymer, it is considered that the elastic modulus of the pressure-sensitive adhesive layer formed is moderately high. From the above, it is presumed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure has excellent high-temperature durability.
[0017] As mentioned above, when a polyfunctional (meth)acrylic acid ester monomer is used as a raw material monomer, the proportion of high molecular weight monomers in the total polymer tends to increase. When the proportion of high molecular weight monomers in the total polymer increases, the viscosity of the adhesive composition increases and the coatability may decrease. Since the adhesive composition of the present disclosure has a relatively low content of structural units derived from polyfunctional (meth)acrylic acid ester monomers in the (meth)acrylic copolymer, the viscosity increase caused by crosslinking between polyfunctional (meth)acrylic acid ester monomers is unlikely to occur. For this reason, it is presumed that the adhesive composition of the present disclosure has excellent coatability.
[0018] In contrast to the present disclosure, in Patent Document 1 (JP Patent No. 6502999; hereinafter the same), a pressure-sensitive adhesive composition containing a (meth)acrylic acid ester polymer, a multifunctional acrylate monomer, and a crosslinking agent is irradiated with ultraviolet (UV) light to harden the composition, thereby forming a pressure-sensitive adhesive layer that does not significantly lift or peel off even when exposed to an environment of 80°C. However, according to the pressure-sensitive adhesive composition described in Patent Document 1, both crosslinking between multifunctional acrylate monomers and crosslinking between a crosslinkable functional group in the (meth)acrylic acid ester polymer and the crosslinking agent are performed, so that the elastic modulus of the pressure-sensitive adhesive layer formed is excessively high. For this reason, the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition described in Patent Document 1 is excessively hard, and is likely to peel off when exposed to an environment of higher temperatures (for example, 105°C).
[0019] However, when the temperature changes in optical components such as polarizing plates, stress may occur due to shrinkage or expansion. If the generated stress is not relieved, the stress remains in the adhesive layer. If the stress remaining in the adhesive layer becomes uneven, for example, a phenomenon in which light leakage occurs in a liquid crystal display device and the display becomes white, that is, a so-called whiteout phenomenon, may occur. In contrast, the pressure-sensitive adhesive composition of the present disclosure can form a pressure-sensitive adhesive layer that is less likely to produce white spots even when exposed to a high-temperature (for example, 105° C.) environment.
[0020] In general, optical members having a pressure-sensitive adhesive layer (so-called pressure-sensitive adhesive layer-attached optical members) are stored in a stacked state. When the pressure-sensitive adhesive layer-attached optical members are stacked, foreign matter may be trapped between the stacked pressure-sensitive adhesive layer-attached optical members. If a foreign matter is trapped, a dent may be formed in the pressure-sensitive adhesive layer, and a mark (so-called a dent) may remain. In contrast, the pressure-sensitive adhesive composition of the present disclosure can form a pressure-sensitive adhesive layer that is less susceptible to dents and has excellent dent resistance.
[0021] [Specific (meth)acrylic copolymer] The pressure-sensitive adhesive composition of the present disclosure contains a (meth)acrylic copolymer [i.e., a specific (meth)acrylic copolymer] that contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, a structural unit derived from a monomer having a carboxy group, and a structural unit derived from a polyfunctional (meth)acrylic acid ester monomer, and in which the content of the structural units derived from the polyfunctional (meth)acrylic acid ester monomer is 0.001% by mass to 0.05% by mass with respect to all structural units. The pressure-sensitive adhesive composition of the present disclosure may contain only one type of specific (meth)acrylic copolymer, or may contain two or more types.
[0022] <Structural Unit Derived from (Meth)acrylic Acid Alkyl Ester Monomer> The specific (meth)acrylic copolymer contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer. The structural units derived from the (meth)acrylic acid alkyl ester monomer can contribute to adjusting the adhesive strength of the pressure-sensitive adhesive layer.
[0023] In the present disclosure, the term "structural unit derived from a (meth)acrylic acid alkyl ester monomer" refers to a structural unit formed by addition polymerization of a (meth)acrylic acid alkyl ester monomer. In addition, the "(meth)acrylic acid alkyl ester monomer" in the present disclosure does not include a monomer corresponding to a monomer having a carboxy group and a monomer corresponding to a polyfunctional (meth)acrylic acid ester monomer.
[0024] The type of the (meth)acrylic acid alkyl ester monomer is not particularly limited. The (meth)acrylic acid alkyl ester monomer is preferably an unsubstituted (meth)acrylic acid alkyl ester monomer. The alkyl group of the (meth)acrylic acid alkyl ester monomer may be linear, branched, or cyclic. The alkyl group preferably has 1 to 22 carbon atoms, more preferably has 1 to 18 carbon atoms, and further preferably has 1 to 12 carbon atoms.
[0025] Specific examples of the (meth)acrylic acid alkyl ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, i-nonyl (meth)acrylate, n-decyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. As the (meth)acrylic acid alkyl ester monomer, for example, at least one selected from n-butyl acrylate (n-BA) and methyl acrylate (MA) is preferable, and n-butyl acrylate (n-BA) is more preferable.
[0026] The specific (meth)acrylic copolymer may contain only one type of constitutional unit derived from a (meth)acrylic acid alkyl ester monomer, or may contain two or more types.
[0027] The content of the structural units derived from the (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic copolymer is not particularly limited, but for example, it is preferably 50 mass% or more, more preferably 50 mass% to 99.9 mass%, even more preferably 65 mass% to 99.8 mass%, and even more preferably 80 mass% to 99.7 mass%, relative to all structural units of the specific (meth)acrylic copolymer. Here, the content of the structural units derived from the (meth)acrylic acid alkyl ester monomer being 50 mass% or more relative to the total structural units of the specific (meth)acrylic copolymer means that the structural units derived from the (meth)acrylic acid alkyl ester monomer are contained as the main component of the structural units constituting the specific (meth)acrylic copolymer.
[0028] <Structural Unit Derived from Monomer Having a Carboxy Group> The specific (meth)acrylic copolymer contains a structural unit derived from a monomer having a carboxy group. When the specific (meth)acrylic copolymer contains a constituent unit derived from a monomer having a carboxy group, the high temperature durability of the formed pressure-sensitive adhesive layer can be improved. Also, when the specific (meth)acrylic copolymer contains a constituent unit derived from a monomer having a carboxy group, the dent resistance of the formed pressure-sensitive adhesive layer can be improved.
[0029] In the present disclosure, a "structural unit derived from a monomer having a carboxy group" refers to a structural unit formed by addition polymerization of a monomer having a carboxy group. In addition, the "monomer having a carboxy group" in the present disclosure does not include monomers that fall under the category of polyfunctional (meth)acrylic acid ester monomers.
[0030] The type of the monomer having a carboxy group is not particularly limited. An example of a monomer having a carboxy group is a monomer having at least one carboxy group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.
[0031] Specific examples of monomers having a carboxy group include acrylic acid (AA), methacrylic acid (MAA), and crotonic acid. ,Ma Examples of the vinyl esters include leic acid, fumaric acid, itaconic acid, glutaconic acid, citraconic acid, ω-carboxy-polycaprolactone mono(meth)acrylates (e.g., ω-carboxy-polycaprolactone (n≒2) monoacrylate), succinic acid esters (e.g., 2-acryloyloxyethyl-succinic acid), vinyl formate, vinyl acetate, vinyl propionate, and vinyl neodecanoate. As the monomer having a carboxy group, for example, acrylic acid (AA) is preferred from the viewpoint of good reactivity with a crosslinking agent (particularly, an isocyanate-based crosslinking agent).
[0032] The specific (meth)acrylic copolymer may contain only one type of structural unit derived from a monomer having a carboxy group, or may contain two or more types.
[0033] The content of the structural units derived from the monomer having a carboxy group in the specific (meth)acrylic copolymer is not particularly limited, but for example, it is preferably 0.05% by mass to 7.0% by mass, more preferably 0.1% by mass to 5.0% by mass, even more preferably 0.3% by mass to 3.0% by mass, and particularly preferably 0.5% by mass to 2.0% by mass, relative to all the structural units of the specific (meth)acrylic copolymer. When the content of the structural unit derived from the monomer having a carboxyl group in the specific (meth)acrylic copolymer is 0.05% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the high temperature durability of the formed pressure-sensitive adhesive layer tends to be superior. Also, when the content of the structural unit derived from the monomer having a carboxyl group in the specific (meth)acrylic copolymer is 0.05% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the dent resistance of the formed pressure-sensitive adhesive layer tends to be superior. When the content of structural units derived from monomers having a carboxy group in the specific (meth)acrylic copolymer is 7.0 mass% or less relative to all structural units of the specific (meth)acrylic copolymer, there is a tendency that a pressure-sensitive adhesive layer that is less likely to produce white spots can be formed even when exposed to a high-temperature environment.
[0034] <Structural Unit Derived from Polyfunctional (Meth)acrylic Acid Ester Monomer> The specific (meth)acrylic copolymer contains a structural unit derived from a polyfunctional (meth)acrylic acid ester monomer, and the content of the structural unit derived from the polyfunctional (meth)acrylic acid ester monomer is 0.001% by mass to 0.05% by mass with respect to all structural units.
[0035] In the present disclosure, the term "structural unit derived from a polyfunctional (meth)acrylic acid ester monomer" refers to a structural unit formed by addition polymerization of a polyfunctional (meth)acrylic acid ester monomer.
[0036] In the present disclosure, the term "polyfunctional (meth)acrylic acid ester monomer" refers to a (meth)acrylate compound having two or more (meth)acryloyl groups in one molecule.
[0037] The polyfunctional (meth)acrylic acid ester monomer may be a difunctional (meth)acrylic acid ester monomer, a trifunctional (meth)acrylic acid ester monomer, or a tetrafunctional or higher functional (meth)acrylic acid ester monomer. As the polyfunctional (meth)acrylic acid ester monomer, for example, from the viewpoint of the coatability of the pressure-sensitive adhesive composition, it is preferable that it is at least one type selected from the group consisting of a difunctional (meth)acrylic acid ester monomer and a trifunctional (meth)acrylic acid ester monomer, and it is more preferable that it is at least one type selected from the difunctional (meth)acrylic acid ester monomer.
[0038] The type of the polyfunctional (meth)acrylic acid ester monomer is not particularly limited. Examples of the polyfunctional (meth)acrylic acid ester monomer include bifunctional (meth)acrylate compounds such as 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate, neopentyl glycol di(meth)acrylate, dimethylol-tricyclodecane di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylethylpropanediol (meth)acrylate, 3-methyl-1,5 pentanediol diacrylate, dimethylol-tricyclodecane diacrylate, EO adduct diacrylate of bisphenol A, PO adduct diacrylate of bisphenol A, and neopentyl glycol / hydroxypivalic acid ester diacrylate; trimethylol propanediol diacrylate, dimethyl ... Examples of the acrylates include trifunctional (meth)acrylate compounds such as propane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and glycerin propoxy triacrylate; tetrafunctional (meth)acrylate compounds such as pentaerythritol tetra(meth)acrylate, sorbitol tetra(meth)acrylate, and ditrimethylolpropane tetra(meth)acrylate; pentafunctional (meth)acrylate compounds such as sorbitol penta(meth)acrylate and dipentaerythritol penta(meth)acrylate; and hexafunctional (meth)acrylate compounds such as dipentaerythritol hexa(meth)acrylate and sorbitol hexa(meth)acrylate.
[0039] The molecular weight of the polyfunctional (meth)acrylic acid ester monomer is not particularly limited, but is preferably in the range of 150 or more and less than 1,200, more preferably in the range of 200 or more and less than 1,000, and even more preferably in the range of 300 or more and less than 800. The polyfunctional (meth)acrylic acid ester monomer tends to have high reactivity during polymerization when its molecular weight is low, and low reactivity during polymerization when its molecular weight is high. If the polyfunctional (meth)acrylic acid ester monomer has an appropriately low reactivity during polymerization, the coatability of the adhesive composition tends to improve, and if the polyfunctional (meth)acrylic acid ester monomer has an appropriately high reactivity during polymerization, the high temperature durability of the adhesive layer formed tends to improve. When the molecular weight of the polyfunctional (meth)acrylic acid ester monomer is 150 or more, the adhesive composition tends to have better coatability. When the molecular weight of the polyfunctional (meth)acrylic acid ester monomer is less than 1,200, the pressure-sensitive adhesive layer formed tends to have better high-temperature durability.
[0040] As the polyfunctional (meth)acrylic acid ester monomer, commercially available products can be used. Examples of commercially available polyfunctional (meth)acrylic acid ester monomers include "A-400" (trade name, chemical name: polyethylene glycol #400 diacrylate, molecular weight: 522, manufactured by Shin-Nakamura Chemical Co., Ltd.), "Viscoat #195" (trade name, chemical name: 1,4-butanediol diacrylate, molecular weight: 198, manufactured by Osaka Organic Chemical Industry Co., Ltd.), "A-1000" (trade name, chemical name: polyethylene glycol #1000 diacrylate, molecular weight: 1138, manufactured by Shin-Nakamura Chemical Co., Ltd.), and "Light Acrylate TMP-A" (trade name, chemical name: trimethylolpropane triacrylate, molecular weight: 298, manufactured by Kyoeisha Chemical Co., Ltd.).
[0041] The specific (meth)acrylic copolymer may contain only one type of structural unit derived from a polyfunctional (meth)acrylic acid ester monomer, or may contain two or more types.
[0042] The content of the structural units derived from the polyfunctional (meth)acrylic acid ester monomer in the specific (meth)acrylic copolymer is 0.001% by mass to 0.05% by mass based on the total structural units of the specific (meth)acrylic copolymer. When the content of the structural units derived from the polyfunctional (meth)acrylic acid ester monomer in the specific (meth)acrylic copolymer is 0.001% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to have excellent high-temperature durability. Also, when the content of the structural units derived from the polyfunctional (meth)acrylic acid ester monomer in the specific (meth)acrylic copolymer is 0.001% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to have excellent dent resistance. From this viewpoint, the content of the structural units derived from the polyfunctional (meth)acrylic acid ester monomer in the specific (meth)acrylic copolymer is 0.001 mass% or more, preferably 0.005 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.015 mass% or more, and particularly preferably 0.02 mass% or more, based on the total structural units of the specific (meth)acrylic copolymer. When the content of structural units derived from polyfunctional (meth)acrylic acid ester monomers in the specific (meth)acrylic copolymer is 0.05 mass% or less relative to all structural units of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive composition tends to have excellent coatability. From this viewpoint, the content of the structural units derived from the polyfunctional (meth)acrylic acid ester monomer in the specific (meth)acrylic copolymer is 0.05 mass% or less, preferably 0.045 mass% or less, more preferably 0.04 mass% or less, even more preferably 0.035 mass% or less, and particularly preferably 0.03 mass% or less, based on the total structural units of the specific (meth)acrylic copolymer.
[0043] <Structural Unit Derived from Monomer Having a Hydroxyl Group> The specific (meth)acrylic copolymer preferably contains a structural unit derived from a monomer having a hydroxyl group. When the specific (meth)acrylic copolymer contains a structural unit derived from a monomer having a hydroxyl group, the high temperature durability of the pressure-sensitive adhesive layer formed can be further improved.
[0044] In the present disclosure, a "structural unit derived from a monomer having a hydroxyl group" refers to a structural unit formed by addition polymerization of a monomer having a hydroxyl group.
[0045] The type of the monomer having a hydroxyl group is not particularly limited. An example of a monomer having a hydroxyl group is a monomer having at least one hydroxyl group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.
[0046] Specific examples of monomers having a hydroxyl group include 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, 3-methyl-3-hydroxybutyl (meth)acrylate, and 1,1-dimethyl-3-hydroxybutyl (meth)acrylate. butyl (meth)acrylate, 1,3-dimethyl-3-hydroxybutyl (meth)acrylate, 2,2,4-trimethyl-3-hydroxypentyl (meth)acrylate, 2-ethyl-3-hydroxyhexyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, glycerin mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, and poly(ethylene glycol-propylene glycol) mono(meth)acrylate. As the monomer having a hydroxyl group, for example, from the viewpoint of good copolymerizability with other monomers, hydroxyalkyl(meth)acrylates are preferred, and from the viewpoint of good compatibility with other monomers and good reactivity with crosslinking agents (particularly isocyanate-based crosslinking agents), hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 1 to 5 carbon atoms are more preferred, hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 2 to 4 carbon atoms are even more preferred, and 2-hydroxyethyl acrylate (2HEA) is particularly preferred.
[0047] When the specific (meth)acrylic copolymer contains a structural unit derived from a monomer having a hydroxyl group, the specific (meth)acrylic copolymer may contain only one type of structural unit derived from a monomer having a hydroxyl group, or may contain two or more types of structural units derived from a monomer having a hydroxyl group.
[0048] When the specific (meth)acrylic copolymer contains a constituent unit derived from a monomer having a hydroxyl group, the content of the constituent unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is not particularly limited, but for example, it is preferably 0.05% by mass to 5.0% by mass, more preferably 0.1% by mass to 3.0% by mass, even more preferably 0.2% by mass to 2.0% by mass, and particularly preferably 0.3% by mass to 1.0% by mass, relative to all constituent units of the specific (meth)acrylic copolymer. When the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 0.05% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to have better high-temperature durability. When the content of the structural unit derived from the monomer having a hydroxyl group in the specific (meth)acrylic copolymer is 0.2% by mass or more relative to the total structural units of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to have better dent resistance as well as high-temperature durability. When the content of structural units derived from monomers having a hydroxyl group in the specific (meth)acrylic copolymer is 5.0 mass% or less relative to all structural units of the specific (meth)acrylic copolymer, there is a tendency that a pressure-sensitive adhesive layer that is less likely to produce white spots can be formed even when exposed to a high-temperature environment.
[0049] <Other building blocks> The specific (meth)acrylic copolymer may contain structural units (so-called other structural units) other than the above-mentioned structural units, i.e., the structural units derived from (meth)acrylic acid alkyl ester monomers, which are essential structural units, the structural units derived from monomers having a carboxy group, and the structural units derived from polyfunctional (meth)acrylic acid ester monomers, as well as the structural units derived from optional structural units having a hydroxyl group, within the scope of not impairing the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0050] Examples of monomers constituting other structural units include aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, aromatic monovinyls such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene, vinyl cyanides such as acrylonitrile and methacrylonitrile, and vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate. Also included are various derivatives of these monomers.
[0051] When the specific (meth)acrylic copolymer contains other structural units, it may contain only one type of other structural unit, or may contain two or more types of other structural units.
[0052] When the specific (meth)acrylic copolymer contains other structural units, the content of the other structural units in the specific (meth)acrylic copolymer is not particularly limited and can be appropriately set depending on the purpose within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0053] <<Molecular weight of specific (meth)acrylic copolymer>> -Weight average molecular weight [Mw]- The Mw of the specific (meth)acrylic copolymer is not particularly limited, but is, for example, preferably 800,000 to 2.5 million, more preferably 1,000,000 to 2.4 million, even more preferably 1.2 million to 2.3 million, and particularly preferably 1.4 million to 2.2 million. When the Mw of the specific (meth)acrylic copolymer is 800,000 or more, the pressure-sensitive adhesive layer formed tends to have better high-temperature durability. When the Mw of the specific (meth)acrylic copolymer is 2.5 million or less, the viscosity of the pressure-sensitive adhesive composition does not become too high, and therefore the pressure-sensitive adhesive composition tends to have better coatability.
[0054] -z average molecular weight [Mz]- The Mz of the specific (meth)acrylic copolymer is not particularly limited, but is, for example, preferably 3.3 million to 10 million, more preferably 3.5 million to 9.9 million, even more preferably 3.7 million to 9.7 million, and particularly preferably 4 million to 9.5 million. When the specific (meth)acrylic copolymer has an Mz of 3.3 million or more, the pressure-sensitive adhesive layer formed tends to have better high-temperature durability. Also, when the specific (meth)acrylic copolymer has an Mz of 3.3 million or more, the pressure-sensitive adhesive layer formed tends to have better dent resistance. When the Mz of the specific (meth)acrylic copolymer is 10 million or less, the pressure-sensitive adhesive composition tends to have better coatability.
[0055] -Ratio of z-average molecular weight (Mz) to weight-average molecular weight (Mw) (Mz / Mw) The Mz / Mw ratio in the specific (meth)acrylic copolymer is preferably from 2.1 to 8.5, more preferably from 2.5 to 6.5, further preferably from 2.5 to 5.5, and particularly preferably from 2.5 to 4.5. When the specific (meth)acrylic copolymer has an Mz / Mw ratio of 2.1 or more, the pressure-sensitive adhesive layer formed tends to have better high-temperature durability. Also, when the specific (meth)acrylic copolymer has an Mz / Mw ratio of 2.1 or more, the pressure-sensitive adhesive layer formed tends to have better dent resistance. When the Mz / Mw in the specific (meth)acrylic copolymer is 8.5 or less, the pressure-sensitive adhesive composition tends to have better coatability.
[0056] As for the Mw and Mz / Mw of the specific (meth)acrylic copolymer, an embodiment in which Mw is 1.4 million to 2.2 million and Mz / Mw is 2.5 to 8.5 is preferred, an embodiment in which Mw is 1.4 million to 2.2 million and Mz / Mw is 2.5 to 6.5 is more preferred, an embodiment in which Mw is 1.4 million to 2.2 million and Mz / Mw is 2.5 to 5.5 is even more preferred, and an embodiment in which Mw is 1.4 million to 2.2 million and Mz / Mw is 2.5 to 4.0 is particularly preferred. When the Mw and Mz / Mw aspects of the specific (meth)acrylic copolymer are as described above, the pressure-sensitive adhesive layer formed tends to have better high-temperature durability, and the pressure-sensitive adhesive composition tends to have better coatability.
[0057] The Mw and Mz of the specific (meth)acrylic copolymer are values determined by the following method, specifically, according to the following (1) to (3). (1) A solution of the specific (meth)acrylic copolymer is applied to a release paper and dried at 100° C. for 1 minute to obtain a film of the specific (meth)acrylic copolymer. (2) Using the film-like specific (meth)acrylic copolymer obtained in (1) above and tetrahydrofuran, a sample solution having a solid content concentration of 0.2% by mass is obtained. Note that the "solid content concentration" here means the mass ratio of the specific (meth)acrylic copolymer in the sample solution. (3) Using gel permeation chromatography (GPC) under the following conditions, the Mw and Mz of the specific (meth)acrylic copolymer are determined in terms of standard polystyrene.
[0058] When there are Ni polymers each having a molecular weight Mi, Mw and Mz are calculated by the following formula. Mw = Σ(Mi 2 ×Ni) / Σ(Mi×Ni) Mz = Σ(Mi 3 ×Ni) / Σ(Mi 2 ×Ni)
[0059] ~Conditions~ Measurement equipment: High-speed GPC [Model: HLC-8220 GPC, manufactured by Tosoh Corporation] Detector: Differential refractometer (RI) [installed in HLC-8220, manufactured by Tosoh Corporation] Column: TSKgel GMH XL Four Tosoh Corporation-made Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100μL Flow rate: 0.8mL / min
[0060] The Mw and Mz of the specific (meth)acrylic copolymer can be adjusted to desired values by adjusting the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, amount of polymerization initiator used, etc. when polymerizing the monomers.
[0061] <<Content of specific (meth)acrylic copolymer>> The content of the specific (meth)acrylic copolymer in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but for example, relative to the total solid content in the pressure-sensitive adhesive composition, is preferably 70 mass% to 99.95 mass%, more preferably 75 mass% to 99.9 mass%, even more preferably 80 mass% to 99.7 mass%, and particularly preferably 85 mass% to 99.5 mass%. In the present disclosure, the "total solid content in the PSA composition" means the total mass of the PSA composition when the PSA composition does not contain a solvent, and means the mass of the residue remaining after removing the solvent from the PSA composition when the PSA composition contains a solvent. In this disclosure, "solvent" means water and organic solvents.
[0062] [Method for producing specific (meth)acrylic copolymer] The method for producing the specific (meth)acrylic copolymer is not particularly limited. The specific (meth)acrylic copolymer can be produced by polymerizing the above-mentioned monomers by a known polymerization method typified by, for example, a solution polymerization method, an emulsion polymerization method, a suspension polymerization method, or a bulk polymerization method. As a polymerization method, a solution polymerization method is preferred in that the processing steps are relatively simple and can be carried out in a short time when preparing the pressure-sensitive adhesive composition of the present disclosure after production.
[0063] In the solution polymerization method, a predetermined organic solvent, a monomer, a polymerization initiator, and a chain transfer agent used as required are generally charged into a polymerization tank, and the mixture is heated and reacted for several hours with stirring at the reflux temperature of the organic solvent in a nitrogen stream. In this case, at least a portion of the organic solvent, the monomer, the polymerization initiator, and the chain transfer agent used as required may be added successively.
[0064] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, and alcohol compounds. More specifically, examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic or alicyclic hydrocarbon compounds such as n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirit, petroleum naphtha, and turpentine oil; ester compounds such as ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate; acetone, methyl ethyl acetate, and the like. Examples of the alcohol compounds include ketones, ketone compounds represented by methyl-i-butyl ketone, isophorone, cyclohexanone, and methylcyclohexanone, glycol ether compounds represented by ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether, and alcohol compounds represented by methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.
[0065] In producing the specific (meth)acrylic copolymer, it is preferable to use an organic solvent that is unlikely to cause chain transfer during the polymerization reaction, such as an aromatic hydrocarbon compound, an ester compound, or a ketone compound. In particular, it is preferable to use ethyl acetate from the viewpoints of the solubility of the specific (meth)acrylic copolymer, the ease of the polymerization reaction, and the like.
[0066] During the polymerization reaction, only one type of organic solvent may be used, or two or more types may be used.
[0067] Examples of the polymerization initiator include organic peroxides and azo compounds that are used in ordinary solution polymerization methods. Specific examples of organic peroxides include t-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-i-propyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-butyl peroxypivalate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane. Specific examples of azo compounds include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile) (ABVN), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyrate) dimethyl. In producing the specific (meth)acrylic copolymer, it is preferable to use a polymerization initiator that does not cause a graft reaction during the polymerization reaction, and it is particularly preferable to use an azo compound.
[0068] In the polymerization reaction, only one type of polymerization initiator may be used, or two or more types may be used.
[0069] The amount of the polymerization initiator used is not particularly limited, and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic copolymer.
[0070] In producing the specific (meth)acrylic copolymer, a chain transfer agent may be used, if necessary. Examples of the chain transfer agent include cyanoacetic acid, alkyl ester compounds of cyanoacetic acid having 1 to 8 carbon atoms, bromoacetic acid, alkyl ester compounds of bromoacetic acid having 1 to 8 carbon atoms, aromatic compounds such as α-methylstyrene, anthracene, phenanthrene, fluorene, and 9-phenylfluorene, aromatic nitro compounds such as p-nitroaniline, nitrobenzene, dinitrobenzene, p-nitrobenzoic acid, p-nitrophenol, and p-nitrotoluene, benzoquinone derivatives such as benzoquinone and 2,3,5,6-tetramethyl-p-benzoquinone, borane derivatives such as tributylborane, carbon tetrabromide, ... Examples of the halogenated hydrocarbon compounds include carbon chloride, 1,1,2,2-tetrabromoethane, tribromoethylene, trichloroethylene, bromotrichloromethane, tribromomethane, and 3-chloro-1-propene, aldehyde compounds such as chloral and furaldehyde, alkyl mercaptan compounds having 1 to 18 carbon atoms, aromatic mercaptan compounds such as thiophenol and toluene mercaptan, mercaptoacetic acid, alkyl ester compounds of mercaptoacetic acid having 1 to 10 carbon atoms, hydroxyalkyl mercaptan compounds having 1 to 12 carbon atoms, and terpene compounds such as pinene and terpinolene.
[0071] When a chain transfer agent is used in producing the specific (meth)acrylic copolymer, the amount of the chain transfer agent used is not particularly limited and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic copolymer.
[0072] The polymerization temperature is not particularly limited, and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic copolymer.
[0073] [Crosslinking Agent] The pressure-sensitive adhesive composition of the present disclosure contains a crosslinking agent. The content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.05 parts by mass or more based on 100 parts by mass of the specific (meth)acrylic copolymer.
[0074] The type of crosslinking agent is not particularly limited. Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, and a metal chelate-based crosslinking agent. Among these, the crosslinking agent is preferably an isocyanate-based crosslinking agent.
[0075] In this disclosure, the term "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in one molecule (so-called polyisocyanate compound). The term "epoxy-based crosslinking agent" refers to a compound having two or more epoxy groups in one molecule (so-called bifunctional or higher epoxy compound). The term "metal chelate-based crosslinking agent" refers to a metal chelate compound that functions as a crosslinking agent.
[0076] The type of the isocyanate-based crosslinking agent is not particularly limited. Examples of the isocyanate crosslinking agent include aromatic polyisocyanate compounds such as xylylene diisocyanate (XDI), diphenylmethane diisocyanate, triphenylmethane triisocyanate, and tolylene diisocyanate (TDI), and aliphatic polyisocyanate compounds or alicyclic polyisocyanate compounds such as hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate, and hydrogenated aromatic polyisocyanate compounds. Further, examples of the isocyanate-based crosslinking agent include dimers, trimers, and pentamers of the above polyisocyanate compounds, adducts of the above polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret forms of the above polyisocyanate compounds.
[0077] As the isocyanate-based crosslinking agent, a commercially available product can be used. Examples of commercially available isocyanate crosslinking agents include "Coronate (registered trademark) HX", "Coronate (registered trademark) HL-S", "Coronate (registered trademark) L", "Coronate (registered trademark) L-45E", "Coronate (registered trademark) 2031", "Coronate (registered trademark) 2037", "Coronate (registered trademark) 2234", "Coronate (registered trademark) 2785", "Aquanate (registered trademark) 200", and "Aquanate (registered trademark) 210" (all manufactured by Tosoh Corporation), "Sumidur (registered trademark) N3300", "Desmodur (registered trademark) N3400", and "Sumidur (registered trademark) N75" (all manufactured by Sumika Covestro Urethane Co., Ltd.), "Duranate (registered trademark) E-405-80T", "Duranate (registered trademark) AE700-100", "Duranate (registered trademark) Examples of such polyurethane foams include "Duranate (registered trademark) 24A-100" and "Duranate (registered trademark) TSE-100" (all manufactured by Asahi Kasei Corporation), as well as "Takenate (registered trademark) D-110N", "Takenate (registered trademark) D-120N", "Takenate (registered trademark) M-631N", "MT-Olestar (registered trademark) NP1200", and "STABIO (registered trademark) XD-340N" (all manufactured by Mitsui Chemicals, Inc.).
[0078] The type of the epoxy crosslinking agent is not particularly limited. Specific examples of epoxy crosslinking agents include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol di ... Examples of such glycidyl ethers include glycerol polyglycidyl ether, resorcinol diglycidyl ether, 2,2-dibromoneopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol polyglycidyl ether, sorbitol polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, tris(glycidyl)isocyanurate, tris(glycidoxyethyl)isocyanurate, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-1,3-benzenedi(methanamine).
[0079] As the epoxy-based crosslinking agent, a commercially available product can be used. Examples of commercially available epoxy crosslinking agents include "TETRAD (registered trademark)-X" and "TETRAD (registered trademark)-C" (both manufactured by Mitsubishi Gas Chemical Company, Inc.).
[0080] The type of the metal chelate crosslinking agent is not particularly limited. Examples of metal chelate crosslinking agents include aluminum chelate compounds such as aluminum monoacetylacetonate bis(ethylacetoacetate), aluminum tris(ethylacetoacetate), and aluminum tris(acetylacetonate), titanium chelate compounds, zirconium chelate compounds, and cobalt chelate compounds.
[0081] As the metal chelate crosslinking agent, commercially available products can be used. Examples of commercially available metal chelate crosslinking agents include Aluminum Chelate A (trade name, chemical name: aluminum tris(acetylacetonate), manufactured by Kawaken Fine Chemicals Co., Ltd.), Aluminum Chelate D (trade name, chemical name: aluminum monoacetylacetonate bis(ethylacetoacetate), manufactured by Kawaken Fine Chemicals Co., Ltd.), and ALCH-TR (trade name, chemical name: aluminum tris(ethylacetoacetate), manufactured by Kawaken Fine Chemicals Co., Ltd.).
[0082] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of crosslinking agent, or may contain two or more types.
[0083] The content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.05 parts by mass or more based on 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.05 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to have excellent high-temperature durability. From such a viewpoint, the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is, relative to 100 parts by mass of the specific (meth)acrylic copolymer, 0.05 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, and particularly preferably 0.4 parts by mass or more. The upper limit of the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but for example, it is preferably 5.0 parts by mass or less, more preferably 4.0 parts by mass or less, even more preferably 3.0 parts by mass or less, and particularly preferably 2.0 parts by mass or less, relative to 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 5.0 parts by mass or less relative to 100 parts by mass of the specific (meth)acrylic copolymer, there is a tendency that a pressure-sensitive adhesive layer that is less likely to produce white spots even when exposed to a high-temperature environment can be formed.
[0084] [Silane coupling agent] The pressure-sensitive adhesive composition of the present disclosure may contain a silane coupling agent. When the pressure-sensitive adhesive composition of the present disclosure contains a silane coupling agent, the adhesiveness of the pressure-sensitive adhesive layer formed to glass can be further improved, and therefore, when the adherend is glass, the high-temperature durability of the pressure-sensitive adhesive layer formed can be further improved.
[0085] The type of silane coupling agent is not particularly limited. Examples of the silane coupling agent include polymerizable unsaturated group-containing silane compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, and 3-methacryloxypropyltrimethoxysilane; thiol group-containing silane compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane; epoxy group-containing silane compounds such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane compounds such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; and tris-(3-trimethoxysilylpropyl)isocyanurate.
[0086] As the silane coupling agent, a commercially available product can be used. Commercially available examples of silane coupling agents include "KBM-402", "KBM-403", and "X-41-1053" (all manufactured by Shin-Etsu Chemical Co., Ltd.).
[0087] When the pressure-sensitive adhesive composition of the present disclosure contains a silane coupling agent, it may contain only one type of silane coupling agent, or may contain two or more types of silane coupling agents.
[0088] When the pressure-sensitive adhesive composition of the present disclosure contains a silane coupling agent, the content of the silane coupling agent is not particularly limited, but is, for example, preferably 0.1 parts by mass to 1 part by mass, more preferably 0.1 parts by mass to 0.8 parts by mass, and even more preferably 0.1 parts by mass to 0.5 parts by mass, relative to 100 parts by mass of the specific (meth)acrylic copolymer. When the content of the silane coupling agent in the pressure-sensitive adhesive composition of the present disclosure is within the above range relative to 100 parts by mass of the specific (meth)acrylic copolymer, the pressure-sensitive adhesive layer formed tends to have better high-temperature durability when the adherend is glass.
[0089] [Organic Solvent] The pressure-sensitive adhesive composition of the present disclosure may contain an organic solvent. When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the coatability can be further improved. As the organic solvent, for example, the same organic solvents as those used in the polymerization reaction of the above-mentioned specific (meth)acrylic copolymer can be mentioned.
[0090] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, it may contain only one type of organic solvent, or may contain two or more types of organic solvent.
[0091] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the content of the organic solvent is not particularly limited and can be appropriately set depending on the purpose.
[0092] [Other ingredients] The pressure-sensitive adhesive composition of the present disclosure may contain components other than the components described above (so-called other components) as necessary, provided that the effects of the composition are not impaired. Examples of other components include various additives such as polymers other than the specific (meth)acrylic copolymer, crosslinking catalysts, tackifiers, antioxidants, colorants (e.g., dyes and pigments), light stabilizers (e.g., ultraviolet absorbers), and antistatic agents.
[0093] When the pressure-sensitive adhesive composition of the present disclosure contains other components, the contents of the other components can be appropriately set within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0094] <<Gel fraction after crosslinking>> The gel fraction after crosslinking of the pressure-sensitive adhesive composition of the present disclosure (so-called gel fraction of the pressure-sensitive adhesive layer) is not particularly limited, but is, for example, preferably 50% by mass or more, more preferably 50% by mass to 90% by mass, even more preferably 60% by mass to 90% by mass, and particularly preferably 70% by mass to 90% by mass. When the pressure-sensitive adhesive composition of the present disclosure has a gel fraction of 50 mass % or more after crosslinking, the pressure-sensitive adhesive layer formed tends to have better high-temperature durability.
[0095] In the present disclosure, the "gel fraction of the pressure-sensitive adhesive composition after crosslinking" refers to the proportion of solvent-insoluble matter measured using ethyl acetate as an extraction solvent. Specifically, the gel fraction of the pressure-sensitive adhesive composition after crosslinking is measured according to the following (1) to (4). (1) About 0.15 g of the crosslinked adhesive composition (i.e., adhesive layer) is attached to a 250 mesh wire net (100 mm x 100 mm) whose mass has been accurately measured using a precision balance, and the wire net is folded five times with the attached adhesive layer facing inward so as to prevent leakage of the gel, to prepare a sample. The mass of the sample is then accurately measured using a precision balance. (2) The obtained sample is immersed in 80 mL of ethyl acetate for 3 days. (3) The sample is taken out, washed with a small amount of ethyl acetate, and dried for 24 hours at 120° C. Then, the mass of the sample after this drying is accurately measured using a precision balance. (4) Calculate the gel fraction using the following formula. Gel fraction (unit: mass%) = (ZX) / (YX) x 100 where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached (unit: g) before immersion, and Z is the mass of the wire mesh with the adhesive layer attached after immersion and drying (unit: g).
[0096] <<Applications>> The application of the pressure-sensitive adhesive composition of the present disclosure is not particularly limited. The pressure-sensitive adhesive composition of the present disclosure can form a pressure-sensitive adhesive layer having excellent high-temperature durability and excellent coatability. In addition, the pressure-sensitive adhesive composition of the present disclosure can form a pressure-sensitive adhesive layer having excellent dent resistance. The pressure-sensitive adhesive composition of the present disclosure has the above-mentioned properties and is therefore suitable for use in, for example, adhering an optical member to an adherend (so-called for use in optical members). Furthermore, the pressure-sensitive adhesive composition of the present disclosure can form a pressure-sensitive adhesive layer that is unlikely to cause white spots even when exposed to a high-temperature environment, and is therefore particularly suitable as a pressure-sensitive adhesive composition for use in polarizing plates, among other optical members. Specific uses include, for example, a use in which a polarizing plate is attached to a liquid crystal cell (specifically, a glass substrate of a liquid crystal cell), a use in which a polarizing plate is attached to an optical film such as a retardation film, and the like.
[0097] [Optical components with adhesive layer] The pressure-sensitive adhesive layer-attached optical member of the present disclosure includes an optical member and a pressure-sensitive adhesive layer provided on the optical member and formed from the pressure-sensitive adhesive composition of the present disclosure. That is, in the pressure-sensitive adhesive layer-attached optical member of the present disclosure, the optical member and the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure are laminated together. The optical member with the pressure-sensitive adhesive layer of the present disclosure has a pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure, and therefore has excellent high-temperature durability. In addition, the optical member with the pressure-sensitive adhesive layer of the present disclosure has a pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure, and therefore is unlikely to produce white spots even when exposed to a high-temperature environment. In addition, the optical member with the pressure-sensitive adhesive layer of the present disclosure has a pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure, and therefore has excellent dent resistance.
[0098] The optical member in the pressure-sensitive adhesive layer-attached optical member of the present disclosure is not particularly limited. Examples of optical members include members constituting devices such as image display devices and input devices (so-called optical devices), and members used in these devices. Specific examples of optical components include polarizing plates, AG (Anti-Glare) polarizing plates, wave plates, retardation plates including 1 / 2, 1 / 4 and other wave plates, viewing angle compensation films, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflection films, transparent conductive films such as ITO (Indium-Tin Oxide) films, prism sheets, lens sheets, and diffusion plates. Examples of materials for optical components include polyolefin resins (e.g., polyethylene and polypropylene), polyester resins (e.g., polyethylene terephthalate (PET)), acetate resins (e.g., triacetyl cellulose resin), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine-based resins.
[0099] As the optical member in the pressure-sensitive adhesive layer-attached optical member of the present disclosure, a polarizing plate is preferred. The polarizing plate includes at least a polarizer, and may be a single polarizer or a laminate of a polarizer and a protective film. That is, the polarizing plate may have a single-layer structure including a polarizer, a two-layer structure including a protective film on one side of the polarizer, or a three-layer structure including protective films on both sides of the polarizer. In the case where the optical member in the pressure-sensitive adhesive layer-attached optical member of the present disclosure is a polarizing plate, examples of the layer configuration include pressure-sensitive adhesive layer / polarizer, pressure-sensitive adhesive layer / polarizer / protective film, pressure-sensitive adhesive layer / protective film / polarizer / protective film, and pressure-sensitive adhesive layer / protective film / polarizer. In addition, between the polarizer and the protective film, between the protective film and the pressure-sensitive adhesive layer, and between the polarizer and the pressure-sensitive adhesive layer, layers such as retardation films (for example, optically functional layers such as an EWV layer, adhesive layers, and easy-adhesion layers) may be present. An example of the polarizer is a polyvinyl alcohol (PVA) film. Examples of the protective film include a triacetyl cellulose (TAC) film, a polycycloolefin (COP) film, a polyethylene terephthalate (PET) film, and an acrylic film.
[0100] The thickness of the pressure-sensitive adhesive layer included in the pressure-sensitive adhesive layer-attached optical member of the present disclosure is not particularly limited. The thickness of the pressure-sensitive adhesive layer is appropriately set depending on, for example, the material and shape of the adherend. The thickness of the pressure-sensitive adhesive layer is generally from 1 μm to 100 μm, preferably from 5 μm to 50 μm, and more preferably from 10 μm to 30 μm.
[0101] In the present disclosure, the "thickness of the pressure-sensitive adhesive layer" means the average thickness of the pressure-sensitive adhesive layer. The average thickness of the pressure-sensitive adhesive layer is a value measured by the following method. The arithmetic mean value of the thicknesses of the adhesive layer measured at 10 randomly selected points in the thickness direction of the adhesive layer is calculated, and the obtained value is regarded as the average thickness of the adhesive layer. The thickness of the adhesive layer is measured using a film thickness meter.
[0102] In the pressure-sensitive adhesive layer-attached optical member of the present disclosure, the exposed pressure-sensitive adhesive layer may be protected by a release film. The release film is not particularly limited as long as it can be easily peeled off from the pressure-sensitive adhesive layer, and examples include resin films that have been surface-treated with a release agent on one or both sides (so-called easy-peeling treatment). An example of the resin film is a polyester film, typically a polyethylene terephthalate (PET) film. Examples of the release agent include silicone-based release agents (eg, silicone), wax-based release agents (eg, paraffin wax), and fluorine-based release agents (eg, fluorine-based resins). The release film protects the surface of the pressure-sensitive adhesive layer until the pressure-sensitive adhesive layer-attached optical member is put to practical use, and is peeled off at the time of use.
[0103] [Method for producing an optical member with a pressure-sensitive adhesive layer] The method for producing the pressure-sensitive adhesive layer-attached optical member of the present disclosure is not particularly limited. The pressure-sensitive adhesive layer-attached optical member of the present disclosure can be produced by a known method. Examples of methods for producing an optical member with a pressure-sensitive adhesive layer of the present disclosure include the following methods. The pressure-sensitive adhesive composition of the present disclosure is applied to the easily peelable surface of a release film to form a coating film on the release film. The formed coating film is then dried to form an adhesive film on the release film. The exposed surface of the formed adhesive film is then brought into contact with an optical member and pressure is applied to transfer the adhesive film to the optical member, thereby forming an adhesive film on the optical member. The formed adhesive film is then cured to form an adhesive layer. In this manner, an optical member with a pressure-sensitive adhesive layer of the present disclosure is obtained.
[0104] Another method for producing the optical member with the pressure-sensitive adhesive layer of the present disclosure includes, for example, the following method. The pressure-sensitive adhesive composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film. Then, the formed coating film is dried to form an adhesive film on the release film. Then, the exposed surface of the formed adhesive film is placed on the easy-release treated surface of a separately prepared release film, and then pressed to produce a double-sided pressure-sensitive adhesive sheet without a substrate. Then, the adhesive film of the prepared double-sided pressure-sensitive adhesive sheet is cured to form an adhesive layer. Then, one of the two release films provided on the double-sided pressure-sensitive adhesive sheet is peeled off, and the exposed adhesive layer is brought into contact with the optical member and pressed, thereby transferring the adhesive layer to the optical member. In this manner, the optical member with the pressure-sensitive adhesive layer of the present disclosure is obtained.
[0105] Another method for producing an optical member with a pressure-sensitive adhesive layer according to the present disclosure can be, for example, the following method. The pressure-sensitive adhesive composition according to the present disclosure is applied to one surface of the optical member to form a coating film on the optical member. The coating film thus formed is then dried to form a pressure-sensitive adhesive film on the optical member. The pressure-sensitive adhesive film thus formed is then cured to form a pressure-sensitive adhesive layer. In this manner, an optical member with a pressure-sensitive adhesive layer according to the present disclosure is obtained.
[0106] The method for applying the pressure-sensitive adhesive composition is not particularly limited. Examples of methods for applying the pressure-sensitive adhesive composition include known methods using a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, knife coater, spray coater, bar coater, applicator, and the like. The amount of the adhesive composition to be applied is not particularly limited, and is appropriately set depending on, for example, the thickness of the adhesive layer to be formed.
[0107] The method for drying the coating film is not particularly limited. Examples of methods for drying the coating film include natural drying, heat drying, hot air drying, and vacuum drying. The drying temperature and drying time of the coating film are not particularly limited, and are appropriately set depending on the thickness of the coating film, the amount of the organic solvent in the coating film, and the like. An example of the drying conditions is drying using a hot air dryer at 70° C. to 120° C. for 30 to 180 seconds.
[0108] The curing is carried out, for example, for 2 to 7 days in an environment with an atmospheric temperature of 20° C. to 50° C. and a relative humidity of 45% to 55% (ie, 45% RH to 55% RH). EXAMPLES
[0109] The pressure-sensitive adhesive composition and the like of the present disclosure will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples as long as it does not deviate from the gist of the disclosure.
[0110] [Preparation of Adhesive Composition] Example 1 Into a reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser, 98.4 parts by mass of n-butyl acrylate [n-BA; acrylic acid alkyl ester monomer], 0.6 parts by mass of 2-hydroxyethyl acrylate [2HEA; monomer having a hydroxyl group], 1.0 part by mass of acrylic acid [AA; monomer having a carboxy group], 0.025 parts by mass of polyethylene glycol #400 diacrylate [product name: A-400, manufactured by Shin-Nakamura Chemical Co., Ltd.] [polyfunctional acrylic acid ester monomer], and 66.7 parts by mass of ethyl acetate [organic solvent] were charged and mixed to obtain a mixture, and then the atmosphere in the reactor was replaced with nitrogen. Next, the mixture in the reactor was heated to 70°C while stirring, and then 0.02 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) [ABVN; polymerization initiator] and 115.0 parts by mass of ethyl acetate were successively added to the mixture in the reactor, and the mixture was held for 6 hours after the addition was completed to complete the polymerization reaction, thereby obtaining a solution containing a polymer. Next, the solution containing the obtained polymer was diluted with ethyl acetate to a solid content concentration of 13.5% by mass, and then cooled to obtain a solution of a (meth)acrylic copolymer.
[0111] The term "solid content" used herein means the mass ratio of the (meth)acrylic copolymer in the (meth)acrylic copolymer solution. The same applies to each of the (meth)acrylic copolymer solutions produced below.
[0112] 100 parts by mass (solid content equivalent) of the (meth)acrylic copolymer solution obtained above, 0.4 parts by mass (solid content equivalent) of Coronate (registered trademark) L-45E (trade name, adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP), solid content concentration: 45% by mass, manufactured by Tosoh Corporation) as a crosslinking agent, 0.3 parts by mass of KBM-403 (trade name, chemical name: 3-glycidoxypropyltriethoxysilane, solid content concentration: 100% by mass, manufactured by Shin-Etsu Chemical Co., Ltd.) as a silane coupling agent, and an appropriate amount of ethyl acetate were thoroughly mixed to adjust the solid content concentration to 8% by mass, thereby obtaining a pressure-sensitive adhesive composition of Example 1.
[0113] [Examples 2 to 14] The same procedure as in Example 1 was carried out except that the composition of the adhesive composition in Example 1 was changed to the composition shown in Table 1, thereby obtaining adhesive compositions of Examples 2 to 14 each having a solid content concentration of 8 mass%.
[0114] [Examples 15 to 25] The same procedure as in Example 1 was carried out except that the composition of the adhesive composition in Example 1 was changed to the composition shown in Table 2, thereby obtaining adhesive compositions of Examples 15 to 25 each having a solid content concentration of 8 mass%.
[0115] [Comparative Examples 1 to 5] The same procedure as in Example 1 was carried out except that the composition of the adhesive composition in Example 1 was changed to the composition shown in Table 3, thereby obtaining each of the adhesive compositions of Comparative Examples 1 to 5, each having a solid content concentration of 8 mass%.
[0116] Weight average molecular weight (Mw) of (meth)acrylic copolymer (unit: 10,000 (in the table, "× 10 4 ")], z-average molecular weight (Mz) of (meth)acrylic copolymer [unit: 10,000 (in the table, "× 10 4 ") and the ratio (Mz / Mw) of the z-average molecular weight (Mz) to the weight-average molecular weight (Mw) in the (meth)acrylic copolymer are shown in Tables 1 to 3. The weight average molecular weight (Mw) and z average molecular weight (Mz) of the (meth)acrylic copolymer were determined by the same method as the weight average molecular weight (Mw) and z average molecular weight (Mz) of the specific (meth)acrylic copolymer described above.
[0117] [Table 1]
[0118] [Table 2]
[0119] [Table 3]
[0120] In Tables 1 to 3, "-" means that the component in that column is not included.
[0121] Details of each monomer shown in Tables 1 to 3 are as follows. <(Meth)acrylic acid alkyl ester monomer> "n-BA": n-butyl acrylate "MA": Methyl acrylate <Monomers having hydroxyl groups> "2HEA": 2-hydroxyethyl acrylate <Monomers having a carboxy group> "AA": acrylic acid <Polyfunctional (meth)acrylic acid ester monomer> -Difunctional (meth)acrylic acid ester monomer- "A-400" [Product name, chemical name: polyethylene glycol #400 diacrylate, molecular weight: 522, manufactured by Shin-Nakamura Chemical Co., Ltd.] "Viscoat #195" (product name, chemical name: 1,4-butanediol diacrylate, molecular weight: 198, manufactured by Osaka Organic Chemical Industry Co., Ltd.) "A-1000" [Product name, chemical name: polyethylene glycol #1000 diacrylate, molecular weight: 1138, manufactured by Shin-Nakamura Chemical Co., Ltd.] -Trifunctional (meth)acrylic acid ester monomer- "TMP-A" [Product name: Light Acrylate TMP-A, Chemical name: Trimethylolpropane triacrylate, Molecular weight: 298, Kyoeisha Chemical Co., Ltd.]
[0122] Details of each crosslinking agent shown in Tables 1 to 3 are as follows. <Isocyanate-based crosslinking agent> "Coronate L-45E" [product name, tolylene diisocyanate compound [adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP)], solid content: 45% by mass, manufactured by Tosoh Corporation] "Takenate D-110N" [product name, xylylene diisocyanate compound [adduct of xylylene diisocyanate (XDI) and trimethylolpropane (TMP)], solid content: 75% by mass, manufactured by Mitsui Chemicals, Inc.] "Sumidur N75" [Product name, hexamethylene diisocyanate compound [biuret form of hexamethylene diisocyanate (HMDI)], solid content: 75% by mass, manufactured by Sumika Covestro Urethane Co., Ltd.] <Epoxy-based crosslinking agent> "TETRAD-X" [product name, solid content: 75% by mass, manufactured by Mitsubishi Gas Chemical Co., Ltd.] <Metal chelate crosslinking agent> "Aluminum Chelate A" [Product name, chemical name: aluminum tris(acetylacetonate), manufactured by Kawaken Fine Chemicals Co., Ltd.] The above "Coronate," "Takenate," "Sumidur," and "TETRAD" are all registered trademarks.
[0123] Details of each of the silane coupling agents shown in Tables 1 to 3 are as follows. "KBM-403" [Product name, chemical name: 3-glycidoxypropyltriethoxysilane, epoxy group-containing silane compound, solid content concentration: 100% by mass, manufactured by Shin-Etsu Chemical Co., Ltd.] "X-41-1053" [product name, epoxy group-containing silane compound, solid content: 100% by mass, manufactured by Shin-Etsu Chemical Co., Ltd.]
[0124] [Preparation of polarizing plate with adhesive layer] A pressure-sensitive adhesive composition was applied onto the surface-treated surface of a release film (type: MRF, thickness: 38 μm, manufactured by Mitsubishi Chemical Corporation) that had been surface-treated with a silicone-based release agent, to form a coating film. The amount of the pressure-sensitive adhesive composition applied was set to an amount that would result in a thickness of the adhesive film described below of 25 μm. Next, air at 100° C. was blown onto the formed coating film at a speed of 3 m / sec for 60 seconds using a hot air circulation dryer, forming an adhesive film with a thickness of 25 μm on the release film. Next, the exposed surface of the formed adhesive film was laminated and attached to one of the triacetyl cellulose (TAC) layer surfaces of a polarizing plate having a structure of a TAC layer / polyvinyl alcohol (PVA) layer containing a polarizer / TAC layer, and then the plate was left to stand for 7 days in an environment with an atmospheric temperature of 23°C and 50% RH to cure the adhesive film, thereby producing a polarizing plate with an adhesive layer having a structure of release film / adhesive layer / polarizing plate (TAC layer / PVA layer / TAC layer).
[0125] [Preparation of film with adhesive layer] A pressure-sensitive adhesive composition was applied onto the surface-treated surface of a release film (type: MRF, thickness: 38 μm, manufactured by Mitsubishi Chemical Corporation) that had been surface-treated with a silicone-based release agent, to form a coating film. The amount of the pressure-sensitive adhesive composition applied was set to an amount that would result in a thickness of the adhesive film described below of 25 μm. Next, air at 100° C. was blown onto the formed coating film at a speed of 3 m / sec for 60 seconds using a hot air circulation dryer to form an adhesive film with a thickness of 25 μm. Next, the exposed surface of the formed adhesive film was laminated onto the surface-treated surface of a separately prepared release film [type: MRF, thickness: 38 μm, manufactured by Mitsubishi Chemical Corporation], and then left to stand for 7 days in an environment with an atmospheric temperature of 23°C and 50% RH to cure the adhesive film, thereby producing a film with an adhesive layer having a structure of release film / adhesive layer / release film.
[0126] [evaluation] 1. Gel fraction The gel fraction was measured according to the following (1) to (4) using the pressure-sensitive adhesive layer peeled off from the pressure-sensitive adhesive layer-attached film prepared above. The results are shown in Tables 4 and 5. (1) About 0.15 g of the adhesive layer is attached to a 250 mesh wire net (100 mm x 100 mm) whose mass has been accurately measured using a precision balance, and the wire net is folded five times with the attached adhesive layer on the inside to prevent leakage of the gel, to prepare a sample. The mass of the sample is then accurately measured using a precision balance. (2) The obtained sample is immersed in 80 mL of ethyl acetate for 3 days. (3) The sample is taken out, washed with a small amount of ethyl acetate, and dried for 24 hours at 120° C. Then, the mass of the sample after this drying is accurately measured using a precision balance. (4) Calculate the gel fraction using the following formula. Gel fraction (unit: mass%) = (ZX) / (YX) x 100 where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached (unit: g) before immersion, and Z is the mass of the wire mesh with the adhesive layer attached after immersion and drying (unit: g).
[0127] 2. Coatability The pressure-sensitive adhesive composition prepared above was applied to the surface of a release film (type: MRF, thickness: 38 μm, manufactured by Mitsubishi Chemical Corporation) that had been surface-treated with a silicone-based release agent, using an applicator (model number: SA202, manufactured by Tester Sangyo Co., Ltd.) at a speed of 2 m / min to 3 m / min. The surface of the coated product after application was visually observed to confirm the presence and degree of coating streaks (so-called streaky patterns caused by coating). The coatability of the pressure-sensitive adhesive composition was then evaluated according to the following evaluation criteria. The results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", "C" and "D" are practically acceptable levels, with "A" being the most preferable.
[0128] -Evaluation criteria- A: No coating streaks were observed on the surface of the coated product. B: Almost no coating streaks were observed at the edges of the surface of the coated product. C: A few coating streaks were observed on the edges of the surface of the coated product, but were within the acceptable range. D: A few coating streaks were observed on the surface of the coated product from the edge to the center, but were within the acceptable range. E: Many coating streaks were observed from the edge to the center of the surface of the coated product, falling outside the acceptable range.
[0129] 3.High temperature durability The polarizing plate with the adhesive layer prepared above was cut into a size of 62 mm × 110 mm. Next, the release film of the cut polarizing plate with the adhesive layer was peeled off, and the surface of the adhesive layer exposed by the peeling was placed on the surface of the adherend shown in Table 4 or Table 5, and then pressure-bonded using a laminator to prepare a sample for evaluating high temperature durability. Next, the prepared high-temperature durability evaluation sample was placed in an incubator maintained at 105°C and left to stand for 500 hours. After the standing time had elapsed, the high-temperature durability evaluation sample was taken out of the incubator and its appearance was visually observed to confirm the presence and extent of foaming, lifting, and peeling. Then, the high-temperature durability of the pressure-sensitive adhesive layer was evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.
[0130] -Evaluation criteria- A: No foaming, lifting or peeling was observed. B: Almost no foaming, lifting or peeling was observed. C: A small amount of foaming, lifting, and peeling was observed, but was within the acceptable range. D: A large amount of foaming, lifting, and peeling was observed, which was outside the acceptable range.
[0131] 4. Whiteout The two polarizing plates with the adhesive layer prepared above were cut into a size of 62 mm × 110 mm to prepare test pieces X and Y. Next, the release films of test pieces X and Y were peeled off, and the surfaces of the adhesive layers exposed by the peeling were placed on both sides of an In-Plane-Switching (IPS) type liquid crystal panel so that the absorption axes of the test pieces were perpendicular to each other, and then the panels were pressed together using a laminator to prepare samples for evaluating white spots. Next, the prepared sample for evaluating white spots was autoclaved (treatment temperature: 50°C, treatment pressure: 5 kg / cm 2(treatment time: 20 minutes). The sample for evaluating blank spots after autoclaving was then left to stand for 24 hours in an environment with an atmospheric temperature of 23°C and 50% RH, and then left to stand for 500 hours in an environment with an atmospheric temperature of 105°C. Next, the sample for evaluating blank spots after standing in the environment with an atmospheric temperature of 23°C and 50% RH was placed on the backlight of a liquid crystal monitor and visually observed to confirm the presence and degree of blank spots. Then, the blank spots were evaluated according to the following evaluation criteria. The results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", "C" and "D" are practically acceptable levels, with "A" being the most preferable.
[0132] -Evaluation criteria- A: No white spots were observed. B: Almost no white spots were observed. C: A very small amount of white spots was observed. D: A small amount of white spots was observed, but within the acceptable range. E: Many blank spots were observed, which was outside the acceptable range.
[0133] 5.Mark resistance The polarizing plate with the pressure-sensitive adhesive layer prepared above was cut into 50 pieces of 100 mm × 110 mm to prepare test pieces, and then the 50 test pieces were stacked with the release film side facing up to prepare a sample for evaluating dent resistance. Next, a 1 kg weight was placed on the prepared sample for evaluating dent resistance in an area of 30 mm × 30 mm, and the sample was left to stand for 3 hours in an environment with an atmospheric temperature of 23°C and 50% RH. After standing, the surface of the release film side of the sample for evaluating dent resistance was observed using a laser microscope (model number: VK-X200) manufactured by Keyence Corporation, and the dent resistance was evaluated according to the following evaluation criteria. The results are shown in Tables 4 and 5. In the following evaluation criteria, "A", "B", and "C" are levels that are not problematic in practical use, with "A" being the most preferable.
[0134] -Evaluation criteria- A: The depth of the dent was in the range of 0 μm or more and less than 1 μm. B: The depth of the dent was in the range of 1 μm or more and less than 3 μm. C: The depth of the dent was in the range of 3 μm or more and less than 5 μm. D: The depth of the dent was 5 μm or more.
[0135] [Table 4]
[0136] [Table 5]
[0137] In Table 4, "-" means that the evaluation for that column was not performed. Details of the adherends listed in Table 4 and / or Table 5 are as follows. "Glass" [Soda glass, manufactured by Matsunami Glass Industry Co., Ltd.] "BASUS" [Stainless steel plate, product name: SUS304, manufactured by Paltec Co., Ltd.] "PET" (Polyethylene terephthalate film, product name: Teijin (registered trademark) Tetoron (registered trademark) Film HPE, thickness: 50 μm, manufactured by Teijin Film Solutions Co., Ltd.) "Polyimide" (Polyimide film, product name: Kapton (registered trademark) 100H, thickness: 25 μm, manufactured by Toray DuPont Co., Ltd.)
[0138] As shown in Table 4, the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of Examples 1 to 25 were excellent in high-temperature durability, and the pressure-sensitive adhesive compositions of Examples 1 to 25 were also excellent in coatability. Furthermore, it was confirmed that the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of Examples 1 to 25 were less likely to produce white spots even when exposed to a high-temperature environment, and that the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of Examples 1 to 25 were excellent in resistance to dents.
[0139] On the other hand, as shown in Table 5, it was confirmed that the adhesive layer formed from the adhesive composition of Comparative Example 1, in which the (meth)acrylic copolymer did not contain a structural unit derived from a polyfunctional (meth)acrylic acid ester monomer, had inferior high-temperature durability compared to the adhesive layers formed from the adhesive compositions of the Examples. It was also confirmed that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 3, in which the (meth)acrylic copolymer contains structural units derived from a polyfunctional (meth)acrylic acid ester monomer but the content of structural units derived from the polyfunctional (meth)acrylic acid ester monomer is less than 0.001 mass% relative to the total structural units, is inferior in high temperature durability compared to the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Examples. It was also confirmed that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Comparative Example 3 is inferior in dent resistance compared to the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of Examples. It was confirmed that the adhesive layer formed from the adhesive composition of Comparative Example 2, in which the content of the crosslinking agent was less than 0.05 parts by mass per 100 parts by mass of the (meth)acrylic copolymer, was inferior in high temperature durability to the adhesive layers formed from the adhesive compositions of the Examples. It was confirmed that the adhesive composition of Comparative Example 4, in which the content of structural units derived from polyfunctional (meth)acrylic acid ester monomers in the (meth)acrylic copolymer exceeded 0.05 mass% with respect to all structural units, had inferior coatability compared to the adhesive compositions of the Examples. It was confirmed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of Comparative Example 5, in which the (meth)acrylic copolymer does not contain a constituent unit derived from a monomer having a carboxy group, is inferior in high-temperature durability compared to the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the Examples. It was also confirmed that the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of Comparative Example 5 is inferior in dent resistance compared to the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the Examples.
Claims
1. a (meth)acrylic copolymer comprising a structural unit derived from a (meth)acrylic acid alkyl ester monomer, a structural unit derived from a monomer having a carboxy group, a structural unit derived from 2-hydroxyethyl acrylate, and a structural unit derived from a polyfunctional (meth)acrylic acid ester monomer, wherein the content of the structural unit derived from the monomer having a carboxy group is 0.05% by mass to 7.0% by mass, the content of the structural unit derived from the 2-hydroxyethyl acrylate is 0.3% by mass to 1.0% by mass, and the content of the structural unit derived from the polyfunctional (meth)acrylic acid ester monomer is 0.001% by mass to 0.05% by mass, based on all structural units; a cross-linking agent; Including, The pressure-sensitive adhesive composition, wherein the content of the crosslinking agent is 0.05 parts by mass or more relative to 100 parts by mass of the (meth)acrylic copolymer.
2. The pressure-sensitive adhesive composition according to claim 1, wherein the polyfunctional (meth)acrylic acid ester monomer is a difunctional (meth)acrylic acid ester monomer.
3. 3. The pressure-sensitive adhesive composition according to claim 1, wherein the polyfunctional (meth)acrylic acid ester monomer has a molecular weight in the range of 200 or more and less than 1,000.
4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the (meth)acrylic copolymer has a weight average molecular weight [Mw] of 1,400,000 to 2,200,000, and a ratio [Mz / Mw] of a z-average molecular weight [Mz] to the weight average molecular weight [Mw] of 2.5 to 4.
5.
5. 5. The pressure-sensitive adhesive composition according to claim 1, wherein the content of the structural units derived from the monomer having a carboxy group in the (meth)acrylic copolymer is 0.1% by mass to 5.0% by mass based on the total structural units of the (meth)acrylic copolymer.
6. The pressure-sensitive adhesive composition according to any one of claims 1 to 5, wherein the content of the crosslinking agent is 0.4 parts by mass or more relative to 100 parts by mass of the (meth)acrylic copolymer.
7. an optical member; a pressure-sensitive adhesive layer provided on the optical member and formed from the pressure-sensitive adhesive composition according to any one of claims 1 to 6; An optical member with a pressure-sensitive adhesive layer comprising:
Citation Information
Patent Citations
Antistatic acrylic pressure-sensitive adhesive and antistatic pressure-sensitive adhesive film using the same
JP2009173721A
Adhesive composition and optical film
JP2011074300A
Laminate and touch panel including the same
JP2013046973A
Adhesive composition, adhesive, and adhesive sheet
JP6502999B2